CFD simulations on the compressor of a mini jet engine-I - Chong, Clarence Yew Keong. (2013)
Unmanned Aerial Vehicles are an important part of today’s military technology as well as its use for surveillance. Mini jet engines are used for some of these UAVs that allows for better performance, range and speed. The following report will focus on the SR-30 jet engine compressor. This report aims to develop a basic framework for future unsteady simulations of the SR-30 compressor to aid experimental study of the SR-30 compressor in the future. SR-30 mini jet engine is one of the most common educational and commercially available compressors, and the study of the flow within its centrifugal compressor is helpful to understand its validity in the battlefield. In the following exercise, engineering software, GAMBIT, FLUENT and AXCENT are used for the construction of the mesh and the CFD simulation respectively.